Exploring the effects of integrating the iPad to improve students' motivation and badminton skills: a WISER model for physical education. Issue 3 (27th May 2018) - Hung, Hui-Chun; Shwu-Ching Young, Shelley; Lin, Kuo-Chin
ABSTRACT: Physical education (PE) is an important subject in higher education that specifically targets motor skills in health-enhancing activities. This study aimed to explore how mobile technology could be integrated into a badminton course to enhance learners' motivation and badminton skills. The experiment was conducted in the university badminton course and a total of 225 college students were involved in this study. The participants were divided into two groups, one who would use technology, the Tablet Course Group (TCG), and the other, the Conventional Course Group (CCG), where conventional face-to-face methods were used. Both qualitative and quantitative approaches were adopted in this study. The results indicate that learning motivation and performance in badminton skills in the TCG were significantly better than those in the CCG. The operation of iPads enabled students to change their holistic views of badminton skill learning and achieve the desired skills at their own pace, and afforded immediate visual feedback on skill learning.